Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1099/vir.0.023176-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of adenovirus from clinical samples through analysis of the hexon and fiber genes

Abstract: Human adenoviruses (HAdVs) are common pathogens associated with a variety of clinical manifestations. Although most infections are self-limiting, HAdVs can cause severe or lethal infections in immunocompromised as well as in healthy individuals. Several HAdVs have recently been characterized as emerging pathogens. In Italy, epidemiological, and especially molecular epidemiological, information on this pathogen is scarce. This study describes the characterization by cell culture, PCR and phylogenetic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
3
8
0
Order By: Relevance
“…Concerning type identification, it was well established that sequence analysis of PCR products in the hexon and/or fiber gene is an appropriate method to type HAdVs [Ariga et al, ; La Rosa et al, ] and our results show a high concordance rates between the two genomic regions. On all the sequenced isolates, only one gave different genotype results in the hexon and the fiber gene: sample C125‐TUN13 which was typed as B3 by sequence analysis in the hexon gene and D8 in the fiber gene.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Concerning type identification, it was well established that sequence analysis of PCR products in the hexon and/or fiber gene is an appropriate method to type HAdVs [Ariga et al, ; La Rosa et al, ] and our results show a high concordance rates between the two genomic regions. On all the sequenced isolates, only one gave different genotype results in the hexon and the fiber gene: sample C125‐TUN13 which was typed as B3 by sequence analysis in the hexon gene and D8 in the fiber gene.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies reported a seasonal increase in the incidence of conjunctivitis cases, especially in spring and summer periods. This can be attributed to the known seasonal high transmission of some aetiological pathogens, or to allergic conjunctivitis which has a relatively higher incidence in spring [Saitoh-Inagawa et al, 1999;Marangon et al, 2007;Matsui et al, 2007;Sambursky et al, 2007;La Rosa et al, 2011;Segal et al, 2014;Erdin et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its hypervariable regions, the hexon region is useful for the classification and recognition of individual serotypes [ 6 ]. Indeed, the broad-range primer pair used in this study has been previously found to be capable of amplifying all known HAdVs [ 4 ]. Positive samples were subsequently tested using an assay targeting the fiber region.…”
Section: Discussionmentioning
confidence: 99%
“…Both the hexon and the fiber genes are considered “hot spots” for base mutations and recombination, which are important driving forces for AdV evolution. Therefore, sequencing the hypervariable regions of the hexon gene and the fiber gene is important for the correct identification and designation of adenovirus strains as demonstrated in previous investigations [ 4 , 7 ]. In the present study, 63% of the positive samples detected in the hexon region were also positive using the fiber assay, and BLAST analysis was concordant with the hexon analysis for these sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation